Diseminasi Teknologi Konservasi Tanah Pada Budidaya Tanaman Sayur Di Lahan Berlereng Di Kabupaten Majalengka - Angga Restu Bagus Mirangga; Yoyon Haryanto; Thomas Widodo (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
Dissemination of soil conservatioan technology in vegetable cultivation on slope in Majalengka. Degradation of agricultural land in the highlands by soil erosion disaster in vegetable cultivation is caused by land management systems without proper soil conservation techniques. Erosion of land by erosion causes a number of nutrients to be carried away resulting in inefficiency in the use of fertilizers. Meanwhile, the dissemination of information on soil conservation as an effort to prevent these threats has not been disseminated optimally. The behavior of farmers who tend not to pay attention to the balance of the ecosystem is due to the fact that information about conservation technology is not well understood. This study aims to determine the factors that influence the behavior of vegetable farmers in the application of soil conservation techniques on sloping land. The research was conducted in Argapura District with a distribution of three villages, namely Argalingga, Argamukti and Sukasari Kidul villages. The method of analysis used multiple linear regression. The results of the analysis show that the length of farming, external factors and the dissemination process have a significant effect on the dissemination of soil conservation technology in vegetable cultivation on sloped land.